Heat shock protein HSP 27 is expressed in all types of basal cell carcinoma in low and high risk UV exposure groups - Bayerl, Christiane; Dorfner, Bettina; Rzany, Berthold; Fuhrmann, E.; Coelho, C. C.; Jung, Ernst G. (European journal of dermatology, 1999)
HSP 27, a marker of differentiation and proliferation, helps the cell in repair processes after environmental stress such as heat, UV-irradiation and oxidative stress. So far, its role on carcinogenesis is not yet understood. HSP 27 was studied immunohistochemically in different types of primary, untreated basal cell carcinoma (BCC) in two populations with different UV exposure habits: descendents from Germany, “Pommern”, living in Brazil (Pommeranos, n = 15), rural workers with high UV exposure and Germans from the region Baden-Württemberg with indoor jobs (n = 14). Age distribution and type of BCC were similar between the Pommeranos and the Germans. Specimens of BCC (n = 15 solid, n = 6 keratotic, n = 4 adenoid, n = 4 fibrotic) were evaluated in cryostat and paraffin sections for HSP 27, HSP 72 and bcl-2. In Pommeranos in Brazil (UV high risk group) versus (vs) inhabitants from Baden-Württemberg (UV low risk group), HSP 27 was expressed in 93% vs 79% in all histological subclasses, HSP 72 in 20% vs 21% and bcl-2 in 93 % in both groups. Antibodies against HSP 27, but not HSP 72, labeled BCC of all types. In contrast to the lack of HSP 27 in squamous cell carcinoma reported in the literature, we found HSP 27 and bcl-2 positive cells in BCC which might characterize the tumour as relatively benign and slow progressing.